FRI0579 What Is The Variability of HAQ over Time in Patients with Rheumatoid Arthritis Treated with Anti-TNF?. (15th July 2016) - Arendse, R.; Haraoui, B.; Choquette, D.; Kelsall, J.; Baer, P.; Sholter, D.; Bensen, W.G.; Bell, M.J.; Teo, M.; Rampakakis, E.; Psaradellis, E.; Osborne, B.; et al.
Abstract : Background: The Health Assessment Questionnaire (HAQ) remains the gold standard for measuring patient-reported functional status in rheumatoid arthritis (RA) and is included among the measures suggested by the American College of Rheumatology for making treatment decisions in routine care. We have previously shown that significant variability exists in the correlation of individual HAQ questions with patient-reported and clinical outcomes. Objectives: The aim of this analysis was to assess, in routine care, the timelines of HAQ improvement as compared to clinical improvement and to examine possible differences in the improvement of individual questions. Methods: BioTRAC is an ongoing, prospective registry of patients initiating treatment for RA, ankylosing spondylitis, or psoriatic arthritis with infliximab (IFX) or golimumab (GLM). Eligible people for this analysis included RA patients treated with IFX who were enrolled since 2002 or with GLM enrolled since 2010. Time to achieving minimal important difference (MID; Δ≥0.22) in HAQ, HAQ≤1, minimal disease (MD) in individual HAQ questions (no or some difficulty), CDAI low disease activity (LDA), or CDAI remission was assessed with the Kaplan-Maier estimator of the survival function and cox regression. Results: 1205 patients (75.3% female) were included with mean (SD) age of 56.0 (13.6) years and disease duration of 8.4 (8.9) years at baseline. Mean (SD) HAQ and CDAI were 1.55 (0.72) and 33.8 (17.4), respectively. Statistically significant and clinically meaningful improvements in both HAQ and CDAI were observed over time. The cumulative probability of achieving HAQ MID, HAQ≤1, CDAI LDA, and CDAI remission by 12 months was 69.5%, 54.5%, 54.1%, and 18.1%, respectively. Time to achieving HAQ MID [Hazard Ratio (95% CI): 3.6 (3.2–4.2)], HAQ≤1 [2.9 (2.6–3.4)], and CDAI LDA [3.1 (2.7–3.6)] was significantly lower as compared to CDAI remission. With respect to individual HAQ questions, at baseline, the most predominant usual activities that patients were unable to do were taking a tub bath (27.9%), reaching and getting down a 5-pound object from the head (21.8%), and doing chores such as vacuuming or yard work (23.2%). In accordance, time to having no or some difficulty in these activities was significantly higher compared to the remaining HAQ items. Conclusions: The results of this analysis show that the timelines for achieving HAQ targets in routine care is comparable to that of achieving CDAI LDA. Significant differences were observed in terms of improvement in individual HAQ items with the inability to take a tub bath, getting heavy overhead objects down, and doing chores being the most persistent. Disclosure of Interest: R. Arendse: None declared, B. Haraoui: None declared, D. Choquette: None declared, J. Kelsall: None declared, P. Baer: None declared, D. Sholter: None declared, W. Bensen: None declared, M. Bell: None declared, M. Teo: None declared, E. Rampakakis: None declared, E. Psaradellis: None declared, B. Osborne Employee of: Janssen Inc., C. Tkaczyk Employee of: Janssen Inc., K. Maslova Employee of: Janssen Inc., F. Nantel Employee of: Janssen Inc., A. Lehman Employee of: Janssen Inc.